Carbon nanotubes decorated by mesoporous cobalt oxide as electrode material for lithium-ion batteries - Wenelska, Karolina; Neef, C.; Schlestein, L.; Klingeler, Rüdiger; Kalenczuk, Ryszard J.; Mijowska, E. (Chemical physics letters, 2015)
We report a facile strategy to synthesize carbon nanotubes decorated by mesoporous cobalt oxide (CNTCo3O4). The mesoporous nature of the nanocomposite is confirmed by transmission electron microscopy, scanning electron microscopy, and X-ray diffraction. The data imply 41wt% mesoporous Co3O4 spheres in the as-prepared material with mean diameters ∼12nm. The nanospheres are embedded in an interconnected network of carbon nanotubes. The specific surface area of CNT@Co3O4 amounts to 463m2/g. Cyclic voltammetry studies show a high activity of the Co2+/Co0 and Co3+/Co2+ redox couples. The conversion reaction is observed and full theoretical capacity is found in the 2nd cycle while significant capacity fading appears upon further cycling. Decorating mesoporous metal oxide nanospheres onto the interconnected electrically conducting network of carbon nanotubes therefore provides a first step towards an electrochemically active material promising for lithium-ion batteries.
Gesehen am 30.06.2020